PENGARUH BUDAYA KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI BAGIAN UMUM SEKRETARIAT DAERAH KOTA BATAM - Hardimon H; Ade Parlaungan Nasution; Yannik Ariyati (Universitas Riau Kepulauan, 2017)
The research was conducted in General Affair Work Of Mayor Office Batam City. The purpose of this study to determine the effect of Work Culture and work satisfaction , either separately (partial) or jointly (simultaneously). In this study, the authors use a sensus of 50 employees taken as from the total population (employees). While this type of data is primary data and secondary data. The primary data source obtained from the questionnaires with employees who are competent in the General Affair Work Of Mayor Office Batam City. While the sources of secondary data obtained of General Affair Work Of Mayor Office Batam City documents and from the literatures related which can support as well as useful for this study. Data gathering technique conducted by way of interviews, questionsand, Observation. Data analysis was performed with descriptive statistics, which are used to describe and given picture of the object studied through a sample of whith sensus motehode data obtained in the field associated with the relevant theories and techniques of the quantitative analysis of the data that has been given a score according to the scale of measurement used the Likert scale and the test results using SPSS (Statistical Product and Service Solution) version 20. From the results of the study authors conclude that the partial work culture (X1) has positive and significant impact on (Y)Performance employees, with the test results for 4,689 and significant 0,000 0,005, while the work satisfaction performance of the employes (X2) has positive and significant impact on work satisfaction (Y) performance employees, with the test results for 3,216 and significant 0,002 0,005. But simultaneously Work culture and Work satisfaction have a positive and significant (strong) toward Employes Performance. Of General Affair of Mayor Office Batam City of 45,583 and significant 0,000 0,005.